2021
DOI: 10.1186/s13690-021-00583-7
|View full text |Cite
|
Sign up to set email alerts
|

Chronic disease multimorbidity among the Canadian population: prevalence and associated lifestyle factors

Abstract: Background Chronic diseases is increasingly becoming one of the most pressing public health concerns in most part of the world, including the Canadian population. The purpose of this study was to estimate the prevalence of multimorbidity in the general population based on 14 major chronic diseases and examine associations with lifestyle/behavioral factors. Methods The data source was the 2015–2016 Canadian Community Health Survey (CCHS). The CCHS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 34 publications
(39 reference statements)
2
26
1
Order By: Relevance
“…Few studies have shown high national level estimates of multimorbidity in Spain and Germany, approximately 60 percent for individuals age 65 years and above [ 8 , 9 ]. Population prevalence studies in Australia, Canada, Spain and several European countries have also reported high prevalence of multimorbidity [ 4 , 10 , 11 ]. Meanwhile, depression in older ages is a public health complication that cannot be ignored [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have shown high national level estimates of multimorbidity in Spain and Germany, approximately 60 percent for individuals age 65 years and above [ 8 , 9 ]. Population prevalence studies in Australia, Canada, Spain and several European countries have also reported high prevalence of multimorbidity [ 4 , 10 , 11 ]. Meanwhile, depression in older ages is a public health complication that cannot be ignored [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review study has revealed that the prevalence of multimorbidity among older adults was found to be more than 55% in different countries [ 14 ]. Despite that, high multimorbidity prevalence has been observed in many developed nations, for instance- the United States, Australia [ 13 ], Canada [ 15 ] & Europe [ 9 , 12 , 16 ]. Interestingly, the older adults from developing nations are inadequately equipped with the multimorbidity challenge; as a result, a study conducted in Vietnam [ 17 ] revealed that more than 40% of older adults had multimorbidity conditions, whereas 69% in China [ 11 ] and 52% in Bangladesh [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the probability for adverse events, non-adherence and drug interactions might be elevated due to the diminished metabolic efficiency for both alcohol and other substances and requires careful management among the older patients drinking in a risky manner. 35 36 Nevertheless, in our study, the prevalence of multimorbidity among the young patients (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) was high (35%). The reason for this might be that our hospital comprises patients from boroughs with low income and low life expectation rates in Norway.…”
Section: Discussionmentioning
confidence: 63%
“…Of the young multimorbid patients (18-34 years) 14.1% used illicit drugs, 14.1% used psychoactive medicinal drugs and 31.4% reported to have psychological distress. Compared with the young patients, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] among multimorbid patients aged ≥35 the prevalence of psychological distress decreased with increasing age (for those aged 35-49 years the prevalence was 30.2%; for those 50-64 years it was 26.3%; 65-79 years: 23.9% and for those >80 years it was 13.8%) while the prevalence of psychoactive medicinal drug use increased substantially with increasing age (for those aged 35-49 years the prevalence was 32.6%; for those 50-64 years it was 45.4%; 65-79 years: 43.8% and for those >80 years it was 41.2%). Illicit drugs were most prevalent among those aged Open access years (16.9%) and decreased substantially with increasing age (for those 50-64 years it was 10.7%; 65-79 years 1.3% and for those >80 years it was 0.8%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation